Lhermitte-Duclos Disease: A case report - Kafle, Prakash; Shilpakar, Sushil K; Sharma, Mohan R; Sedain, Gopal; Pradhanang, Amit K; Ghimire, Ram Kumar; Rajbhandari, Binod (Nepal Journal of Neuroscience, 2017)
Available with full text. Nepal Journal of Neuroscience, Volume 14, Number 1, 2017, Page: 28-31